Effects of Hypoxia on Cardiomyocyte Metabolism: An In Vitro and In Vivo Comparative Study - Zaman S. Hamza; Ruqaya Munther Jalil Ewadh; Raad Habeeb Al-Asadi (Journal of Biomedicine and Biochemistry, 2025)
Hypoxia significantly alters cardiomyocyte metabolism, contributing to myocardial injury during ischemic events. In this study, cardiomyocytes cultured under hypoxic conditions were compared to cardiac tissues from rats subjected to experimental myocardial infarction. Both models demonstrated a metabolic shift from oxidative phosphorylation to anaerobic glycolysis, upregulation of hypoxia-inducible factor 1-alpha (HIF-1α), and increased lactate production. The in vivo model also revealed structural changes and fibrosis. Understanding these metabolic adaptations is crucial for developing therapeutic strategies aimed at preserving cardiac function during ischemia and reperfusion.